ANALYSIS OF ECONOMIC AND FINANCIAL CONDITIONS FOR ATTRACTING FOREIGN INVESTMENTS IN THE AGRICULTURAL SECTOR (Academicia Globe: Inderscience Research, 2025)
This article provides an in-depth analysis of the economic and financial conditions for attracting foreign investment into Uzbekistan’s agricultural sector. Based on global best practices and the specific characteristics of the country’s agricultural policy, the study scientifically explores the significance of foreign investment and its impact on the stability and innovative development of agriculture.In particular, the research examines the current investment climate in the agrarian sector, the level of development of financial infrastructure, institutional reforms, and the effect of guarantees related to land and property rights on investor confidence. Additionally, the effectiveness of government-provided tax incentives, subsidies, and credit-financing mechanisms is assessed, along with their potential to enhance the attractiveness of foreign capital. Using modern scientific and methodological approaches such as statistical analysis, comparative studies, and SWOT analysis, the article develops practical recommendations to increase the investment appeal of Uzbekistan’s agricultural sector. Special attention is given to issues such as the influence of land ownership and usage rights on investment risks, the insufficient availability of financial services in agriculture, and the lack of foreign investor-oriented financial instruments in the sector.